Analysis of Knowledge Sharing and Learning Organization on Employee Performance through Employee Engagement at PT Surabaya Industrial Estate Rungkut - Rafi Athallah Riva'i; Gendut Sukarno (Dinasti Publisher, 2024)
Knowledge is a key strategic resource for organizations, knowledge facilitates transformation in the divisions of the company. Therefore, the implementation of an employee knowledge improvement program is important for the company. This study aims to examine the Influence of knowledge sharing and learning organization on employee performance through employee engagement at PT Surabaya Industrial Estate Rungkut. This research uses primary data through distributing questionnaires. This research involved 60 employees as respondent with a partial least square (PLS) based structural equation modeling (SEM) data analysis method through SmartPLS 4 software. The results showed that knowledge sharing significantly and positively impacts on employee performance and learning organization significantly and positively impacts on employee performance. Knowledge sharing significantly and positively impacts on employee performance through employee engagement and learning organization significantly and positively impacts on employee performance through employee engagement.